The role of artificial intelligence in consumers’ brand preference for retail banks in Hong Kong - Ho, Shirie Pui Shan; Chow, Matthew Yau Choi (Journal of financial services marketing, 2024)
Artificial intelligence (AI) technologies are increasingly integral to our world, as they serve as the foundation for new value propositions and distinctive customer experiences. AI is crucial for offering better customer experiences, which strengthen the consumer–brand relationship and brand differentiation. Based on the stimulus–organism–response model, this study examined the influence of AI on brand preference for retail banks in Hong Kong. Structural equation modeling was used to analyze 300 responses collected from a questionnaire survey of Generation Z subjects. The findings indicate that AI marketing efforts affected brand experience, brand preference, and repurchase intention. Among AI marketing efforts, information, accessibility and customization exerted influences on brand experience, while interaction had no significant impact on it. Brand experience also mediated the relationship between AI marketing efforts and brand preference. The study will help retail banks to design AI marketing activities and formulate better marketing and branding strategies for customer acquisition and retention.